Influence of Solvents on Spin Transition of \([Fe(ABPT)_2(C(CN)_3)_2]\) Spin-crossover Molecule - Tuan, Nguyen Anh (Communications in Physics, 2013)
We present a density-functional study of the inuence of solvents on the geometricstructure and the electronic structure of the low-spin and high-spin states of [Fe(ABPT)2 (C(CN)3)2] molecule with abpt = 4-amino-3,5-bis(pyridin-2-yl)-1,2,4-triazole, in order to explore more aboutthe way to control spin-crossover behavior of transition metal molecules. Our calculated resultsdemonstrated that the geometric structure of molecule under consideration is only slightly changedby solvents. However, typical quantities of the electronic structure and spin-transition of thismolecule such as the atomic charge, the magnetic moment of Fe ion, the HOMO-LUMO gap, andthe spin-state energy dierence are varied as a function of dielectric constant of solvents. Theyreach saturation values with increasing dielectric constant. These results should give some hintsto control spin transition temperature of spin-crossover molecules.